2020
DOI: 10.1371/journal.pone.0239392
|View full text |Cite
|
Sign up to set email alerts
|

Fermented yellow mombin juice using Lactobacillus acidophilus NRRL B-4495: Chemical composition, bioactive properties and survival in simulated gastrointestinal conditions

Abstract: The purpose of the present study was to evaluate yellow mombin (Spondias mombin L.) juice as a vehicle for the Lactobacillus acidophilus NRRL B-4495 probiotic. The initial pH and fermentation temperature conditions were optimized by central composite rotational design. The beverage was evaluated for its chemical composition, bioactive properties, microbiological stability, survival in simulated gastrointestinal conditions and sensory analysis. The ideal conditions for probiotic juice production were an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…QDA qualifies the type and quantifies the intensity of sensory properties immediately after sensory stimulation (Stone & Sidel, 2004). Ribeiro et al (2020) evaluated the fermented yellow mombin juice using Lactobacillus acidophilus NRRL B-4495 and concluded that the juice formulation without fermentation was the most accepted (64.7%). Even so, this acceptance was considered low (<70.0%).…”
Section: Discussionmentioning
confidence: 99%
“…QDA qualifies the type and quantifies the intensity of sensory properties immediately after sensory stimulation (Stone & Sidel, 2004). Ribeiro et al (2020) evaluated the fermented yellow mombin juice using Lactobacillus acidophilus NRRL B-4495 and concluded that the juice formulation without fermentation was the most accepted (64.7%). Even so, this acceptance was considered low (<70.0%).…”
Section: Discussionmentioning
confidence: 99%
“…The inoculum (10% v/v) (Section 2.3) was aseptically added to the pasteurized juice to obtain the non-fermented beverages (SYN and SYNa). After adding the inoculum (10% v/v) for the fermented beverages (SYNf and SYNfa), the formulations were incubated at 30 • C for 18 h [18]. The fructooligosaccharides powder was added for a final concentration of 25 g/L.…”
Section: Obtaining Potentially Synbiotic Yellow Mombin Beveragesmentioning
confidence: 99%
“…The viability can be also influenced by the storage temperature, the nutritional composition of food, and the probiotic strain used [17]. Furthermore, probiotic cultures can alter sensory characteristics of the product and can impair the acceptance of the product [18], which is essential to obtain a pleasing sensory profile for market success [10].…”
Section: Introductionmentioning
confidence: 99%
“…The strain was deposited on the China General Microbial Culture Collection Management Center, CGMCC No 1.5409. The viability of freeze-dried L. casei was evaluated by plating on MRS agar, according to methodology described by Ribeiro et al (11). For L. casei treatment, freeze-dried L. casei at concentration of 2 x 10 10 CFU/g was suspended using sterile water and diluted to obtain concentration of 1 × 10 9 CFU/mL.…”
Section: Lacticaseibacillus Casei Preparationmentioning
confidence: 99%
“…The dishes were incubated at 37°C under anaerobic conditions for 72 hours. The results are expressed as a logarithm of Colony Forming Units per gram of a sample (log 10 CFU/g), as previously described (11).…”
Section: Fecal Lactic Acid Bacteria Analysismentioning
confidence: 99%